Empowering Learning: Unveiling The Impact Of Independence Learning And Teaching Styles On Student Engagement At SMP Islam Plus Al-Azhar, Mojokerto City - Ihrisa Qurrotun Nada; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
Active learning as a provision for forming quality human resources. There are two factors that influence students' active learning, namely learning independence and the teacher's teaching style. The purpose of this study is to examine the influence of self-directed learning and the instructional approaches of teachers on the engagement of students in active learning at Al-Azhar Islam Plus Middle School in Mojokerto City. The quantitative research method was employed, and data were collected through the distribution of questionnaires to students at Al-Azhar Islam Plus Middle School, Mojokerto City. A total of 95 students will be recipients of the questionnaires. The analysis of the gathered data will involve the utilization of multiple linear regression techniques. This research uses two independent variables, namely learning independence and the teacher's teaching style towards active learning as the dependent variable. The results of this research indicate that there is a significant influence between learning independence and the teacher's teaching style on students' active learning. Students who are independent in learning are generally more active, search for information themselves, and have inner motivation to learn. Apart from that, the way the teacher teaches also has a big role in shaping the level of student activity. Teaching approaches that involve interaction, stimulate critical thinking, and encourage student participation can create higher levels of active learning